Development of Theory and Practice of the Knowledge Management System as a Component of the Digital Economy - Olga V. RUZAKOVA (Communications of International Proceedings, 2020)
This article considers the development of the theory and practice of knowledge management as a component of the digital economy. The relevance of the article is due essentially to the powerful development of the digital economy and its impact on all areas of the state’s economy. The purpose of the study is to develop theoretical provisions on the strategy, organization, and economics of the knowledge management system as a component of the enterprise management system as a whole. The strategy of the knowledge management system and methods of its formation are determined. The structure of the knowledge management system has been developed with the definition of three main outlines and their description. This structure can be used in practical work on modeling the components of the system. The technological and methodological components of the organization of the knowledge management system are determined. In the course of the research, the author determined the economy, including the budget and the formation of the system's profit, and also considered the method of multi-tier cost accounting for the functions of ABC (Activity Based Costing) and its practical application. The work uses some methods of system analysis (structuring, classification, modeling, analogy, and graphic methods).
Keywords: Knowledge Management System; Organization of Knowledge Management; Strategy of Knowledge Management; Knowledge Economy; Business-Process.